University of Surrey Roehampton, London Subtitling: the long journey to academic acknowledgement - Díaz Cintas, Jorge (The Journal of Specialised Translation, 2004)
The present article is part of a wider translation project from Spanish carried out by Juan Abad, Judith Harling, Yuka Miyakita, Mark Seager and Christina Wiggins, students at the University of Surrey Roehampton. Audiovisual translation seems to have been absent from academic exchanges on translation until very recently. Focusing solely on subtitling, this article starts by taking a look at the reasons behind this state of affairs. It then presents the reader with a detailed account of the research that has taken place in this field, both outside and in Spain. After an overview of the topics, figures, publications and conferences that have had an impact on subtitling, the paper points to the direction of possible avenues of research. Although the future seems very promising for this field of research, the article finishes with a section highlighting some of the challenges that lie ahead of us.